Entropy measures of Y-junction based nanostructures - Ali N.A. Koam; Muhammad Azeem; Muhammad Kamran Jamil; Ali Ahmad; Khalil Hadi Hakami (Ain Shams Engineering Journal, 2023)
Recent research on nanostructures proved their importance and implementation in various areas. In drug delivery systems, medicine and pharmaceutical, biological sensors, photodetectors, transistors, optical and electronic devices, in all these topics nanostructures are implemented directly or indirectly. Future advanced electronic devices are a motivation for the discovery of carbon nanotubes made Y-shaped junctions. Electronic switches, amplifiers, and three-terminal transistors are of great interest due to their interaction with Y-junctions. The concept of entropy determines the uncertainty of a system or network. Concepts of entropy are also commonly used in biology, chemistry, and applied mathematics. Entropy in the form of a graph can be classified into several types based on the requirements. Graph-based entropy was introduced in 1955. Edge-weighted-based entropy is one of the types of entropy. In this study, we look closely at the abstract form of Y-shaped junctions. For the generic view of Y-shaped junctions, we developed some edge-weight-based entropy formulas. On Y-shaped junctions, we discussed some edge-weighted and topological index-based concepts.